It's all in how you fall - Henning, Sarah (Poppy : Little, Brown and Company, 2022)
After an injury forces fifteen-year-old gymnast Caroline to quit competing, her older brother's best friend Alex promises to help her find a new signature sport, and, in return, she offers to set him up on a date with her former teammate.